2015
DOI: 10.4103/0253-7613.161258
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial drug prescribing patterns for community-acquired pneumonia in hospitalized patients: A retrospective pilot study from New Delhi, India

Abstract: Objective:The objective of this study was to determine patterns and frequency of antimicrobial drug use among hospitalized patients with community-acquired pneumonia (CAP).Methodology:A retrospective 5 years (April 2007–March 2012) detailed medical record review of patients diagnosed with CAP and discharged to home from Non-Intensive Care Unit respiratory medicine wards of two public hospitals in Delhi.Results:A total of 261 medical records were analyzed. Over the 5 years, 82.0% (2007–08), 78.6% (2008–09), 59.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Penicillins are recommended as the first line antibiotics for treatment of respiratory tract infections [12]. However, recent trends indicate that penicillins are increasingly substituted by second and third generation cephalosporins for treatment of respiratory tract infections in both outpatient [13, 14] and inpatient settings [15, 16]. In a study between December 2007 and November 2008 which conducted exit interviews of patients with upper respiratory tract infections showed that in private clinics, cephalosporins were prescribed to 39% of patients followed by fluoroquinolone (24%), penicillins (19%) and macrolides (11%) [13].…”
Section: Changing Prescribing Practicesmentioning
confidence: 99%
“…Penicillins are recommended as the first line antibiotics for treatment of respiratory tract infections [12]. However, recent trends indicate that penicillins are increasingly substituted by second and third generation cephalosporins for treatment of respiratory tract infections in both outpatient [13, 14] and inpatient settings [15, 16]. In a study between December 2007 and November 2008 which conducted exit interviews of patients with upper respiratory tract infections showed that in private clinics, cephalosporins were prescribed to 39% of patients followed by fluoroquinolone (24%), penicillins (19%) and macrolides (11%) [13].…”
Section: Changing Prescribing Practicesmentioning
confidence: 99%
“…With the passage of time, the burden of bacterial infections is showing an ascending trend and this is largely due to the generation of resistance mechanisms by bacteria [ 2 , 3 ]. Among the various patterns of resistance, reports across the globe continue to emerge on the resistance to aminoglycoside antibiotics which otherwise have been reported as highly potent drugs against life threatening Gram-negative bacterial infections [ 4 , 5 ]. Aminoglycosides act primarily by impairing bacterial protein synthesis through binding to prokaryotic ribosomes via 16S ribosomal RNA (16S rRNA) and by disrupting the bacterial cell membrane integrity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…[20] In an Australian study, ceftriaxone and azithromycin combination was used for 56% of the patients[21] and one-third of patients with CAP in an Indian study received macrolide and a beta-lactam. [22]…”
Section: Discussionmentioning
confidence: 99%